Biocompatibility of a Novel Cyanoacrylate Based Tissue Adhesive: Cytotoxicity and Biochemical Property Evaluation - Lee, Young Ju; Jung, Gyeong Bok; Choi, Samjin; Lee, Gihyun; Kim, Ji Hye; Son, Ho Sung; Bae, Hyunsu; Park, Hun-Kuk (PLOS ONE, 2013)
Cyanoacrylate (CA) is most widely used as a medical and commercial tissue adhesive because of easier wound closure, good cosmetic results and little discomfort. But, CA-based tissue adhesives have some limitations including the release of cytotoxic chemicals during biodegradation. In previous study, we made prepolymerized allyl 2-CA (PACA) based tissue adhesive, resulting in longer chain structure. In this study, we investigated a biocompatibility of PACA as alternative tissue adhesive for medical application, comparing with that of Dermabond® as commercial tissue adhesive. The biocompatibility of PACA was evaluated for short-term (24 hr) and long-term (3 and 7 days) using conventional cytotoxicity (WST, neutral red, LIVE/DEAD and TUNEL) assays, hematoxylin-eosin (H&E) and Masson trichrome (MT) staining. Besides we examined the biochemical changes in cells and DNA induced by PACA and Dermabond® utilizing Raman spectroscopy which could observe the denaturation and conformational changes in protein, as well as disintegration of the DNA/RNA by cell death. In particular, we analyzed Raman spectrum using the multivariate statistical methods including principal component analysis (PCA) and support vector machine (SVM). As a result, PACA and Dermabond® tissue adhesive treated cells and tissues showed no difference of the cell viability values, histological analysis and Raman spectral intensity. Also, the classification analysis by means of PCA-SVM classifier could not discriminate the difference between the PACA and Dermabond® treated cells and DNA. Therefore we suggest that novel PACA might be useful as potential tissue adhesive with effective biocompatibility.